Analisis Pengaruh Faktor-Faktor Building Information Modeling terhadap Tingkat Penerapan dan Kinerja Proyek pada Proyek Design and Build - Yanuar Kurniawan; Agus Suroso (Syntax Corporation, 2023)
This study aims to determine the effect of the level of BIM application on project performance (cost, quality, time). Building Information Modeling (BIM) is a collaborative approach in construction project management that uses digital information models to integrate all aspects of a project, from planning to execution. The research method carried out in this study is using quantitative methods by observation using questionnaires. The results of the analysis show that the factors that influence the application of BIM have a significant influence on the level of BIM application in Design and Build projects. In addition, the level of BIM implementation also positively impacts overall project performance, with increased time efficiency, reduced costs, and improved quality of project results. This research provides a better understanding of the importance of implementing Building Information Modeling (BIM) in Design and Build projects, as well as identifying factors that can effectively improve the level of project implementation and performance. Thus, this research is expected to be a guideline for stakeholders in the construction industry to optimize the benefits of using BIM in future projects.